Developing Carbene Footprinting Mass Spectrometry to Interrogate Protein-Ligand Interactions - Lloyd, James (2023)
The interaction of proteins with small molecules or other proteins is essential to almost every cellular process. Because of this importance and the potential implication in disease pathogenesis, proteins are attractive drug targets. Improved knowledge of these relationships greatly benefits our understanding of key biological processes and aids in drug discovery efforts. Techniques that provide structural information on a short time scale and employ small amounts of sample are highly desired. Carbene footprinting is a recently developed mass spectrometry-based chemical labelling technique that probes protein interactions and conformation. The work reported in this thesis aims to further develop the application of carbene footprinting to the study of protein structure and interactions by mapping the contact interfaces of several clinically relevant protein systems.